Lymph node ratio as an independent prognostic factor for breast cancer-related mortality in patients with node-positive breast cancer - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Aim: This study assessed whether prognostic information could be obtained in patients with lymph node (LN)-positive breast cancer based on their LN ratios (LNRs) and explored the relationships between other potential prognostic factors and survival. Setting and Design: This was a retrospective clinical study. Materials and Methods: This study included 608 women with node-positive nonmetastatic breast cancer. Clinical and pathologic data were retrospectively evaluated. The median age was 51 years (range: 23-84 years). All patients received adjuvant radiotherapy after radical surgery. A total dose of 50 Gy was administered to the chest wall or breast and LN regions with 2 Gy daily fractions. A 10-Gy boost was administered to the breast tumor bed. The cutoff value of LNR was defined as low risk (<0.21) in 278 patients, intermediate risk (0.21-0.65) in 217 patients, and high risk (>0.65) in 113 patients. Prognostic variables included patient characteristics, disease characteristics, and interventional factors. The primary endpoint was overall survival and the secondary endpoint was breast cancer-related mortality. Statistical Analysis Used: Statistical analyses were performed using the Kaplan-Meier method, log-rank test, and Cox regression analysis. P value was required to be <0.05. Results: Within a median follow-up period of 95.4 months (range: 5-232.4 months), overall survival rates for 10 and 15 years were 66% and 53%, respectively. Multivariate analysis revealed that LNR (P = 0.026), estrogen receptor status (ERS) (P = 0.021), age (P = 0.04), and smoking (P = 0.024) were independent significant prognostic factors for overall survival. Breast cancer-related mortality rates at 10 and 15 years were 70.7% and 60%, respectively. LNR (P = 0.03) and ERS (P = 0.002) were independent significant prognostic factors for breast cancer-related mortality. Conclusions: LNR and ERS were significant prognostic factors for survival at all endpoints.
Keywords: Breast cancer; prognostic factors; the lymph node ratio; ADJUVANT CHEMOTHERAPY; BRITISH-COLUMBIA; AXILLARY NODES; EXCISED NODES; SURVIVAL; NUMBER; PREDICTORS; RECURRENCE; PERCENTAGE; WOMEN